Social Strategy in Stunting Prevention: Analysis of the GENTING Program (Foster Parents Movement to Prevent Stunting) by the DPC IPeKB Pangkalpinang to Minimize Stunting Cases in Pangkalpinang City - Saputri, Mei; Yulianto, Farros Dwi; Kraoudila, Surindah; Janila, Janila; Sulaiman, Aimie (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study discusses the social strategies implemented by the DPC IPeKB Pangkalpinang in efforts to prevent and reduce stunting through the Gerakan Orang Tua Asuh Cegah Stunting (GENTING) program. The background of this research stems from the persistently high and fluctuating stunting rates in Pangkalpinang City each year, as well as the differing interpretations between the government and the community regarding the meaning of stunting itself. This research employs a qualitative approach using a case study method, with data collected through interviews and observations involving families at risk of stunting, posyandu cadres, and the management of DPC IPeKB Pangkalpinang. The findings indicate that the community, particularly families at risk of stunting, generally do not understand the scientific concept of stunting. Most people still interpret stunting as a physical condition of a child being small or thin, or as a hereditary trait, rather than as a result of chronic malnutrition. Furthermore, some community members still associate stunting with traditional beliefs, such as “penyakit budak” (child illness), which is perceived as a non-medical or supernatural disorder. Through the GENTING program, DPC IPeKB plays an active role in bridging this gap in understanding by conducting direct outreach, providing nutritional assistance, offering health education, and guiding families at risk of stunting. The program has proven effective in raising public awareness about the importance of nutrition, hygiene, and healthy parenting patterns. Theoretically, this research is analyzed using Peter L. Berger’s (1990) theory of social construction, which emphasizes that social change occurs through three stages: externalization, objectivation, and internalization. The GENTING program has proven to be an important instrument in shaping new social awareness, as communities begin to understand that stunting is not a matter of fate or heredity, but a preventable condition through improved lifestyle and nutritional intake